Recruitment and Retention Lessons for the New Orleans Police Department - Rostker, Bernard D. (RAND Corporation, 2007)
This study presents recommendations to improve recruiting and retention in the New Orleans Police Department (NOPD). The recommendations, tailored to the unique circumstances of the NOPD, include using civilian employees for some jobs now performed by officers; developing a proactive recruiting program; providing housing; increasing the frequency of promotion examinations; eliminating the backlog of promotions; restructuring compensation; establishing a first-responders charter school; and rebuilding the police infrastructure.